On harmonic state estimation of power system with uncertain network parameters - Chawasak Rakpenthai (2018)
This paper addresses the problem of harmonic state estimation (HSE) of a power system whose network parameters are known to bewithin certain tolerance bounds. The harmonic voltage and current phasors at harmonics of interest are measured by using adequate numbers of phasor measurement units. The HSE is formulated based on the weighted least squares (WLS) criterion as a parametric interval linear system of equations. The solutions are obtained as interval numbers representing the outer bound of state variables. A method for adjusting the weight used in WLS which takes uncertain network parameters into consideration is also proposed. The proposed HSE algorithm is applied to the three-phase power systems and the results from numerical experiments show that the bounds of state variables obtained by the proposed method agree with those estimated by performing Monte Carlo simulations but with much shorter computation time. © 2013 IEEE.